Experimental study of the reaction 6Li + 154Sm at 7 MeV/u using the Saci-Pererê spectrometer (2016)
Abstract. In this work we analyze experimental data of the nuclear reaction between 6 3Li + 154 62Sm . The experimental data come from the gamma-particle coincidence experimental technique using Saci-Pererê γ-ray spectrometer and Pelletron accelerator located at the Instituto de Física da Universidade de São Paulo, Brazil. The Saci-Pererê spectrometer is designed to study nuclear reaction processes such as inelastic scattering, transfer, break-up and fusion (complete and incomplete). The aim of the experiment is to study the different reaction mechanisms of the 6Li + 154Sm nuclear reaction. In particular, to measure inelastic differential cross section of the excited states of the 154Sm. The projectile 6Li is weakly bound and the 154Sm target is quadrupole deformed in its ground state. Little information about weakly bound nuclei interacting with deformed nuclei is known. In those kind of reactions the continuum states of the weakly bound projectile are expected to play an important role. The projectile 6Li was accelerated above the coulomb barrier energy at 42 MeV (VB ≈ 28.7 MeV), thus various kind of reactions are produced. The inelastic scattering of 154Sm is observed in coincidence with Z = 3 nuclei in a ∆E Vs. E spectrum. The γ-ray spectrum shows only the first exited state of the 154Sm. However, the experimental results do not provide enough statistics to measure the angular-particle distribution and to compare with the theoretical predictions. The others identified products are influenced by the easy breaking of 6Li. The first product identified by the breaking up of 6Li is 156Eu. This nucleus is formed after the absorption of a deuteron by the target (incomplete fusion process). The second identified product by breaking of 6Li is 157Gd. This result is confirmed by the coincidence of gamma-rays with Z = 2 nuclei. 157Gd is formed after of the absorption of an alpha particle by the target (incomplete fusion process). Gamma-rays in coincidence with Z = 1 nuclei suggest the emission of one neutron